Trichoderma como bioestimulante do crescimento de mudas de cajueiro-anão - Santos, João Marcos Rodrigues dos (2020)
The availability of dwarf cashew seedlings in quantity and with high quality is essential to meet the demand promoted by the resumption of cajuculture in Brazil. Among the various existing technologies, the use of biological inputs such as Trichoderma can be an alternative for the production of quality dwarf cashew seedlings. Thus, the objective was to evaluate the ability of Trichoderma strains to promote the growth of rootstock and grafted dwarf cashew seedlings. Two experiments were carried out in a nursery located in the Experimental Field of Pacajus. In the experiment for the production of the 'CCP 06' rootstock, the design used was entirely randomized with three treatments (control and application of Trichoderma longibrachiatum and T. asperellum at the time of sowing), and for the production of grafted cashew seedlings. 'BRS 226' were seven treatments (control, application of T.longibrachiatum and T. asperellum at sowing, application of T. longibrachiatum and T. asperellum after grafting and application of T. longibrachiatum and T. asperellum at sowing and after sowing grafting). The strains of T. longibrachiatum and T. asperellum were obtained from the rhizosphere of banana trees and commercial product respectively. In each experiment the plants were evaluated for height, stem diameter, number of leaves, leaf area, dry leaf mass, aerial part, stem, roots and total, in addition to the assessment of nutritional status via leaves. The inoculated strains were re-isolated and purified to quantify the production of indole-3- acetic acid, siderophores and calcium phosphate solubilization in vitro. In the experiment for the production of the rootstock, the T. longibrachiatum strain promoted increases in plant height, leaf area, stem diameter, dry mass of leaves, stem, aerial and total, in relation to the commercial strain and the witness. In the production of grafted seedlings, the strains influenced the variables: stem diameter, leaf area and dry leaf mass. Both strains produced siderophores and solubilized calcium phosphates in vitro, however, they did not produce indole-3-acetic acid, both in the rootstock production and in the grafted seedling phase. The treatments did not differ regarding the accumulation of macro and micronutrients in the rootstock leaves and the grafted dwarf cashew seedlings. The T. longibrachiatum strain promoted an increase in the growth of „CCP 06‟ used as a rootstock for grafted dwarf cashew seedlings. The use of the strains of T. longibrachiatum and T. asperellum proved to be advantageous only for the stem diameter of grafted dwarf cashew tree 'BRS 226'.